Methyl carbazate energetic complexes: Transition metal perchlorates – Syntheses, crystal structures and properties. (15th October 2016) - Sitong, Chen; Weiming, Guo; Bo, Zhang; Tonglai, Zhang; Li, Yang
Graphical abstract: A series of transition metal (1 Mn(II), 2 Ni(II), 3 Cu(II), 4 Zn(II) and5 Cd(II)) methyl carbazate perchlorate energetic complexes were synthesized and fully characterized. Non-isothermal reaction kinetics parameters and Tp, Tb, Δ S ≠, Δ H ≠ and Δ G ≠ values were calculated. Variation of the outer coordination sphere could reduce the thermal stability but immensely improve the decomposition rate and the sensitivities. Abstract: A series of transition metal (1 Mn(II), 2 Ni(II), 3 Cu(II), 4 Zn(II) and5 Cd(II)) methyl carbazate perchlorate energetic complexes were synthesized in aqueous solution. The crystal structures were determined by single-crystal X-ray diffraction. The complex [Cu(MCZ)2 ](ClO4 )2 belongs to the triclinic P 1 ¯ space group. The Mn(II), Ni(II), Zn(II) and Cd(II) complexes all are monoclinic, P 21 / c space group. Their thermal stabilities were investigated using differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA). All the compounds show good thermal stabilities (1, 2, 4 and5 under 200 °C;3 under 160 °C). Non-isothermal reaction kinetics parameters, the critical temperatures of thermal explosion, Δ S ≠, Δ H ≠ and Δ G ≠ were calculated. Their impact and friction sensitivities were tested, and their sensitivity levels are acceptable. The coordinated perchlorates reduce the thermal stability, but improve the decomposition rate immensely as well as the sensitivities.